1991
DOI: 10.1007/bf02660164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrophobe type and extent of branching on environmental response factors of nonionic surfactants

Abstract: A number of ethoxylated nonionic surfactants differing in hydrophobe branching and chainlengths have been evaluated for environmental responses. Screening biodegradation tests show that those nonionics having more than one methyl group per hydrophobe degrade considerably slower than those having less extensive branching. Continuous flow-through activated sludge tests, simulating actual waste treatment, show that the more highly branched nonionics biodegrade more slowly and less extensively than those with less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…Brij-35) are considered readily biodegradable. Kravetz et al [22] observed 80% primary degradation in 28 days for such compounds. Meanwhile, CTAB belongs to the quaternary ammonium compounds which are also biodegradable through different pathways.…”
Section: Waste Generationmentioning
confidence: 99%
“…Brij-35) are considered readily biodegradable. Kravetz et al [22] observed 80% primary degradation in 28 days for such compounds. Meanwhile, CTAB belongs to the quaternary ammonium compounds which are also biodegradable through different pathways.…”
Section: Waste Generationmentioning
confidence: 99%
“…Extensive branching of the hydrophobic part of non-ionic surfactants of the ''hard''-type, such as nonylphenol ethoxylates (NPE), was shown to slow their biodegradation considerably, as do their high concentration in the effluents and low temperatures (Kravetz et al, 1990).…”
Section:  :   mentioning
confidence: 99%
“…Some biodegradation of these latter components could explain the results: the central cleavage of the molecule, leading to the formation of polyethylene glycol and aliphatic alcohol, is the most important pathway for the aerobic biodegradation of AAEs and this mechanism is all the more easy since the alkyl chain is short [24].…”
mentioning
confidence: 99%